Creativity Unbound. Rethinking Audiovisual Authorship in the Artificial Intelligence Era - Sonego, Allegra; Iapalucci, Greta (The Matter of Intellectual Property: Studying the Economic, Political and Cultural Nodes of the Contemporary Media Industries. 15th Media Mutations International Conference, 2025)
The advent of artificial intelligence (AI) has reshaped the debate on authorship in audiovisual media, challenging traditional notions of intellectual property and creative agency. This paper explores the evolution of authorship from early cinematic theories to the rise of collaborative and intertextual media contents, ultimately questioning how AI-generated creative products should be attributed. By analyzing case studies, including AI-generated films, TV shows and deepfake applications, we assess the implications of AI as both a creative tool and a co-author. Legal and cultural perspectives are considered, addressing copyright concerns and the function of AI in media production. Our study argues that while AI introduces new complexities in creative ownership, human oversight remains essential in shaping and interpreting AI-assisted content. Ultimately, building on the ongoing transformation of media creation in the digital age, we claim that AI’s role in authorship must be examined on a case-by-case basis.